Nobody to play with? The implications of leisure coordination - Stephen P. Jenkins; Lars Osberg (University of Essex, Institute for Social and Economic Research (ISER), 2003)
The core hypothesis of this paper is that an individuals time use choices may be contingent on the time use choices of others, because the utility derived from leisure time often benefits from the presence of companionable others inside and outside the household. We develop this idea using a model of time use, and demonstrate that it is consistent with the behaviour of British working couples in the 1990s. We show, first, that there is clear evidence of the synchronisation of working hours by spouses. Second, we report estimates indicating that propensities to engage in associative activity depend not only on spousal activity, but also on the availability of Suitable Leisure Companions outside the household.
Keywords: 330